Dynamic Resource Management of Real-Time Edge Services for Intelligent Vehicular Networks: A Case Study - Gilly, Katja; Filiposka, Sonja; Alcaraz Carrasco, Salvador; Mishev, Anastas (Publishing House Technologija, 2019)
The Internet of Vehicles requires high bandwidth and low latency services to unleash the potential of fully connected vehicles. Thus, the offloading proposals that successfully manage massive real-time service requests from vehicle nodes are needed. In this paper, we analyse the dynamic resource management for intelligent vehicular networks based on Multi-access Edge Computing architecture services. Using a combination of CloudSim and SUMO simulators, we present a case study of infotainment services in the city centre of Alicante, in Spain, that shows a high degree of optimality both in service allocation and migration when considering dense urban environments.
Keywords: Edge computing; Resource management; Intelligent vehicles; 5G mobile communication